PREDICTION OF STOCK RETURN ON BANKING INDUSTRY AT THE INDONESIA STOCK EXCHANGE BY USING MVA AND EVA CONCEPTS - Willem, Meigi Fransiska; Saerang, David P. E.; Tumewu, Ferdinand (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Capital market is a tool that can be used to mobilize funds. To mobilize fund, capital market uses fundamental and technical analysis. In order to support the analysis, Steward (1989), Consultant Management Service in the US, in Astuti (2006), introduced MVA and EVA concepts to be used as measurement of financial performance to overcome the shortcomings of traditional accounting. The objectives of this research are to analyze the effect of MVA and EVA on stock returns of banking industry at Indonesian Stock Exchange. Theories support this research are Stock Return, MVA and EVA. To achieve the objectives, the research method used is associative with multiple regression analysis. The populations used in this study are listed banking industry at Indonesia Stock Exchange (IDX) in 2009 to 2012 with 10 banks as the samples. Results and conclusions are the effect of MVA and EVA to Stock Return do not have significant effect simultaneously; partially, MVA have negative relationship and does not have significant effect on Stock Return, while EVA have positive relationship but does not have significant effect on Stock Return. These indicate that MVA and EVA concept is not appropriate to be used to predict stock returns on banking industry. Perhaps traditional accounting is better to measure than MVA and EVA. This concept can be used in other industries to measure the company performance. Keywords: Stock Return